The Buzzword: Employee Engagement. Does Person-Organization Fit Contribute to Employee Engagement? - (:unkn) unknown (UNIV TEHRAN, 2015)
This study aimed to investigate the relationship between person-organization value fit and employee engagement, as well as to develop a new scale for measuring organizational engagement. We considered person-organization fit with a degree of similarity between personal values and organizational values. These values were measured by the Organizational Culture Profile (OCP). We divided employee engagement into two dimensions. These were work engagement and organizational engagement. Work engagement was measured by the Utrecht Work Engagement Scale (UWES). To measure organizational engagement, we constructed a 15-item Organizational Engagement Scale. We achieved this by examining its definition and existing scales. In order to collect data, available employees provided us with the relevant information. A total of 285 employees answered the questionnaires of this study. These employees worked in organizations that function in the service sector in Istanbul. Our reliability and factor analyses revealed that the Organizational Engagement Scale has a high reliability and two sub dimensions. These were named organizational vigour and organizational dedication. Regression analyses confirmed our research hypotheses: we found person-organization positively contributed to both work engagement and organizational engagement. However, we found that the contribution of person-organization fit to organizational engagement was more powerful than to work engagement.
Keywords: Employee engagement; Organizational engagement; Values; Person-organization fit; Work engagement; WORK ENGAGEMENT; PSYCHOLOGICAL CONDITIONS; JOB DEMANDS; CULTURE; RESOURCES; SOCIALIZATION; BURNOUT; PEOPLE